A case report of drug-induced liver injury due to the infliximab biosimilar CT-P13 on switching from original infliximab in a patient with Crohn’s disease - Shin Kashima; Koji Sawada; Kentaro Moriichi; Mikihiro Fujiya (Therapeutic Advances in Drug Safety, 2022)
Inflammatory bowel diseases (IBDs) are chronic immune disorders of unclear etiology. Tumor necrosis factor (TNF) inhibitors are effective for IBD treatment and are cost-effective because they reduce hospital admissions and are associated with fewer surgery requirements and a better quality of life in IBD patients. A large number of clinical trials of infliximab biosimilar (CT-P13) have suggested that the administration of biosimilars provides high efficacy and safety similar to that of the originators, with a lower cost, so switching from the original to a biosimilar is considered an acceptable treatment. While several abnormalities of blood examination have been observed in patients with CT-P13 administration, no cases of drug-induced liver injury (DILI) caused by CT-P13 has been reported. A 23-year-old woman had been diagnosed with Crohn’s disease and was treated with original infliximab (O-IFX) for 9 years. She developed severe jaundice 1 month after switching from O-IFX to CT-P13. Serologic tests of autoimmune and hepatitis viruses were negative, and ultrasonography, computed tomography, and magnetic resonance cholangiopancreatography revealed no abnormalities. A liver biopsy showed prominent pericentral canalicular cholestasis, without features of steatosis or sclerosing cholangitis, which was consistent with drug-induced cholestasis. The cholestasis improved 10 weeks after the discontinuation of CT-P13, and no DILI redeveloped even after re-switching from CT-P13 to O-IFX. This is the first report of DILI due to switching from O-IFX to CT-P13. While the efficacy and safety of CT-P13 are considered equal to those of O-IFX, clinicians need to be alert for certain severe DILIs when switching from O-IFX to CT-P13 with careful monitoring and appropriate treatment. Plain Language Summary A case report of drug-induced liver injury due to switch from original infliximab to infliximab biosimilar Inflammatory bowel disease (IBD) is characterized by chronic inflammation of the entire gastrointestinal tract, although its etiology has largely been unclear. Tumor necrosis factor (TNF) inhibitors are effective for IBD treatment and are cost-effective because they reduce hospital admissions and are associated with fewer surgery requirements and a better quality of life in IBD patients. A biological medicinal product that contains a version of the active substance of an already authorized biological medicinal product. Biosimilars of TNF inhibitors, such as CT-P13, are thought to possess equal efficacy and safety to the original with a lower cost, so switching from the original to a biosimilar considered an acceptable treatment. While several serious adverse reactions of TNF inhibitors have been reported, drug-induced liver injury (DILI) is uncommon, and liver dysfunction due to the administration of CT-P13 has not been reported in IBD patients. We herein report the first case of DILI due to CT-P13 after switching from original infliximab (O-IFX) in a patient with Crohn’s disease. While the efficacy and safety of CT-P13 are considered equal to those of O-IFX, clinicians need to be alert for certain severe DILIs when switching from O-IFX to CT-P13 with careful monitoring and appropriate treatment.